Caspase-1/IL-1β represses membrane transport of GluA1 by inhibiting the interaction between Stargazin and GluA1 in Alzheimer's disease - Xunhu Gu; Hanjun Wu; Yuqin Xie; Lijun Xu; Xu Liu; Wei Wang (BMC, 2021)
Abstract Background Alzheimer's disease is a neurodegenerative disease. Previous study has reported that caspase-1/IL-1β is closely associated with Alzheimer's disease. However, the biological role of caspase-1/IL-1β in Alzheimer's disease has not been fully elucidated. This study aimed to explore the mechanism of action of caspase-1/IL-1β in Alzheimer's disease. Methods Mouse hippocampal neurones were treated with Aβ1-42 to induce Alzheimer's disease cell model. APP/PS1 mice and Aβ1-42-induced hippocampal neurones were treated with AC-YVAD-CMK (caspase-1 inhibitor). Spatial learning and memory ability of mice were detected by morris water maze. Flow cytometry, TUNEL staining, Thioflavin S staining and immunohistochemistry were performed to examine apoptosis and senile plaque deposition. Enzyme linked immunosorbent assay and western blot were performed to assess the levels of protein or cytokines. Co-Immunoprecipitation was performed to verify the interaction between Stargazin and GluA1. Results AC-YVAD-CMK treatment improved spatial learning and memory ability and reduced senile plaque deposition of APP/PS1 mice. Moreover, AC-YVAD-CMK promoted membrane transport of GluA1 in APP/PS1 mice. In vitro, Aβ1-42-induced hippocampal neurones exhibited an increase in apoptosis and a decrease in the membrane transport of GluA1, which was abolished by AC-YVAD-CMK treatment. In addition, Stargazin interacted with GluA1, which was repressed by caspase-1. Caspase-1/IL-1β inhibited membrane transport of GluA1 by inhibiting the interaction between Stargazin and GluA1. Conclusions Our data demonstrate that caspase-1/IL-1β represses membrane transport of GluA1 by inhibiting the interaction between Stargazin in Alzheimer's disease. Thus, caspase-1/IL-1β may be a target for Alzheimer's disease treatment.